Konsep Diri Remaja dari Keluarga Broken Home - Oktavian, Chikita Irma; Mahmudah, Siti (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2014)
Adolescence is a period of transition or the transition from childhood into adulthood. At this time individuals experiencing various changes, both physically and psychologically. This study aims yo determine the self-concept teen from a broken home. The method used was a qualitative research method. Data collection using interviews, observation and documentation. Subject used in the study were adolescents who experienced a broken home. The result of this study are the self-concept of adolescents who experience a broken home leads to positive. Factors that can affect an individuals self-concept formation is significant other who could be close friends or family, the environment, the role of social factors and physical state is of note primarily by teenagers and a factor that was instrumental in the formation of an individual self-concept.